The legacy of James Diego Vigil - Tapia, Mike (The Oxford handbook of gangs and society, 2024)
The dean of Chicana/o gang studies, James Diego Vigil, pioneered a long-running era of such research starting in the late 1970s. The Los Angeles barrio gang milieu of his youth and subsequent Chicana/o activist experiences became the foundation for the intellectual frameworks he would later develop as a scholar. This chapter examines select aspects of Diego’s life and work in relation to the historiography and current state of this genre of gang research. Diego is known for delineating the macro-level forces, local community processes, and individual psychodynamics that produce barrio gangs. These themes are presented in the context of the vast scholarship comprising Chicana/o gang studies that developed over several decades since the days of Diego’s own social protest arrests by the LAPD in the 1970s. His ostracism from public education helped to form his unique academic trajectory and legacy heretofore unmatched by any protégé.